Faktor - Faktor Yang Berhubungan Dengan Gangguan Kesehatan Pada Pekerja Mebel Kayu Di Kelurahan Oesapa Kecamatan Kelapa Lima Kota Kupang - Ida, Maria Rosiana; Doke, Soni; Salmun, Johny A. R. (Timorese Journal of Public Health, 2019)
Workers of wood furniture are employes who are at risk for health issues. The issues are commonly caused by work-related condition. This study aimed to analyze the relationship between the length of work, use of Personal Protective Equipment (PPE), the period of working, type of job with health problems in wooden furniture workers in OesapaVillageKelapa Lima Sub-District Kupang 2017. Type of research used was analytical survey research with cross-sectional approach. This research was conducted in wooden furniture manufactures from March to June 2017. The population in this research was 55wooden furniture workers. Research sampling technique used was total sampling. Data was collected by questionnaire and interview. Data analysis technique used was chi-square test with significance level of α = 0,05. The results showed that the usage of PPE (0,00), type of work (0,00) were significantly related to health disorder at wooden furniture workers. There was no correlation observed between duration of work (0,54), period of working (0,92) and health disorder at wooden furniture workers.